2004
DOI: 10.1039/b404064c
|View full text |Cite
|
Sign up to set email alerts
|

Taming ring morphology in 2D Co(OH)2 Liesegang patterns

Abstract: We present here novel expermients on the formation of Liesegang rings in 2D. We consider the system of propagating Co(OH) 2 bands studied extensively in 1D, from the viewpoint of a large number of considerations. In this paper, we focus on morphological aspects and, in the first part, we seek to steer the appearance of the pattern to achieve a pre-determined morphology. We aim at attaining three main features: minimizing the re-dissolution of Co(OH) 2 at the back of the propagating pattern, clearing the fuzzy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(61 citation statements)
references
References 23 publications
5
54
1
Order By: Relevance
“…It is shown that for a typical Liesegang pattern, the band spacing increases as B 0 increases, but decreases as A 0 increases. This formulation is consistent with experimental observation [25,26].…”
Section: Matalon-packter Lawsupporting
confidence: 91%
“…It is shown that for a typical Liesegang pattern, the band spacing increases as B 0 increases, but decreases as A 0 increases. This formulation is consistent with experimental observation [25,26].…”
Section: Matalon-packter Lawsupporting
confidence: 91%
“…9. In contrast with the field free and DC cases [1,13,14,36], the spacing is distinctly larger at lower Co 2+ concentrations.…”
Section: Varying the Concentration At Constant Field Strength And Frecontrasting
confidence: 53%
“…Periodic precipitation can be used for potential applications in material science [12], if effective techniques to control and design these patterns can be found. Several studies treated special effects in this broad dynamical system, such as the variation of the concentrations of the electrolytes [13,14], the application of an electric field [15][16][17][18][19], the addition of impurities to the gel medium [20], or the change in the pH field [21,22]. Other studies compared and contrasted the cases where direct [24,23] or revert [25] spacing is obtained, and considered the formation of polymorphic structure [26,27].…”
Section: Introductionmentioning
confidence: 98%
“…In Liesegang landscapes, the morphological appearance of the bands is governed by the coupling between diffusion, chemical reactions and the field response of the co-precipitate ions. A diversity of wave propagation features were demonstrated in the presence of an electric field, in HgI 2 [7,8], Cr(OH) 3 [9], Ag 2 Cr 2 O 7 [10,11] and Co(OH) 2 [12,13] precipitate systems. A wealth of wave structures and exotic behavior was also obtained from the conjecture of the dynamics of diffusion-precipitation patterning media subjected to applied electric fields [11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%